2009
DOI: 10.1039/b914923f
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant foams doped with laponite: unusual behaviors induced by aging and confinement

Abstract: International audienceWe report results on foams stabilized by surfactant (sodium dodecyl sulfate) and containing clay particles (laponite). We have studied how these foams age with time (drainage and coarsening) and their rheological properties. Due to the doping with laponite, which provides an additional time evolution of the foaming fluid itself, unusual behaviors are observed: especially, drainage arrest and re-start and enhanced elasticity are observed as a function of time. These results can be interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 29 publications
4
51
0
1
Order By: Relevance
“…They can be used as sacrificial templates for the production of macroporous materials [1,2] , in food and cosmetics or for a large variety of other applications [3][4][5][6] . Although a strong effort has been made for understanding the aging of foams [7] and consequently for increasing their stability and properties via their chemical formulation [8][9][10] , there still does not exist a system which would exhibit high foamability in parallel with drastic reductions of the aging processes, leading to huge lifetimes. It must be mentioned however that the stability can be increased alternatively but by using gelator within the foam stock solution [11] .…”
Section: ((Dedication----optional))mentioning
confidence: 99%
“…They can be used as sacrificial templates for the production of macroporous materials [1,2] , in food and cosmetics or for a large variety of other applications [3][4][5][6] . Although a strong effort has been made for understanding the aging of foams [7] and consequently for increasing their stability and properties via their chemical formulation [8][9][10] , there still does not exist a system which would exhibit high foamability in parallel with drastic reductions of the aging processes, leading to huge lifetimes. It must be mentioned however that the stability can be increased alternatively but by using gelator within the foam stock solution [11] .…”
Section: ((Dedication----optional))mentioning
confidence: 99%
“…For this purpose, rheology is of prime importance to study the flow behaviour of foams [3,5,6,68]. Abivin et al [47] have studied the rheological properties of foamy oil by using a controlled stress rheometer under pressure.…”
Section: Tests and Specific Tools For Studying Foaming And Defoaming mentioning
confidence: 99%
“…Thus one finds general concepts relating to foam generation and stability of fluid-based foam pertinent to all types of foam. For example the surface tension will determine the energy required to create a bubble in the media, and the foaming liquid rheology controls the drainage and approach between adjacent bubbles [3,5,6]. Beyond these general concepts more specific physical chemical aspects must be addressed to understand individual systems.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate drop sizes give the least stable foams. Highly concentrated emulsions can have a yield stress that is sufficient to stop drainage [11,12]. Goyon et al [11] showed that drainage could be induced by shear once the applied stress exceeds the yield stress of the emulsions.…”
Section: Introductionmentioning
confidence: 99%